(3YfhGf GdReGf aj JQGLe GdTjhN hGdCbQGfs - (3GdHbGYj , EHQGgje Hf YeQ Hf MSf GdQHGW Hf Ydj Hf CHj HcQ GdHbGYj GdTGaYj, HQgGf GdOjf CHh GdMSf,J (B885 (3g` s
(3ChdgG (B:s
(3GdMeO ddg HQC GdNdjbI cghdkG hTjhNkG s
(3QJHg Ydi GdMQha hgj fSNI eUhQI ef fSNI chHQjdi RGOg HGdBSJGfgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B56 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B71s
(3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B178 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B188 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JGQjN (B1001) s
Keywords: (3GdJGQjNs